The Abbreviation in News Text on Asharq Al-Awsat Online Newspaper/ الاختصار في نصوص الجريدة الإلكترونية الشرق الأوسطالاختصار في نصوص الجريدة الإلكترونية الشرق الأوسط - Imtinana Nafilah Azmi; Nurul Murtadho; Yusuf Hanafi (Al-Arabi: Jurnal Bahasa Arab dan Pengajarannya = Al-Arabi: Journal of Teaching Arabic as a Foreign Language, 2022)
An abbreviation is a new form of the word that combines two or more words representing the original word. In Arabic discourse, this is not new but still not familiar among Arabic learners. The primary purpose of this research is to find, understand, and analyze the phenomenon of abbreviation in Arabic in forms and processes contained in the al-Uula rubric in the online media of the Asharq Al-Awsat newspaper in March 2020. This research is library research which uses a qualitative approach with documentation techniques on data collection and data analysis techniques developed by Miles and Huberman. Based on the research 31 data were obtained for Arabic abbreviations. The results showed four types of abbreviation processes; mukhtaṣar with 10 data, al-naḥt with 1 data, and ikhtizaal with 20 data. The Abbreviation in Arabic Fusha, in particular, requires a lot of further studies to become a reference and insight that are easily accessible to Arabic readers and learners.